Development Of Employee Attendance Control System Based On Google Maps Range (Case Study: Cv. Dhivatech Consultindo) - Yola Febrianto Erdi Mufti Muhammad; Sumarno Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
Employee attendance is data that shows the daily attendance of employees in a company. Data that can be generated from an employee's absence is the time of arrival and departure of employees as evidence of attendance at work in the office. Then, employees who do not come to work can also know their status whether the person concerned has permission or is sick. Attendance system on CV. Dhivatech Consultindo is currently still manual, the leadership confirms the presence of employees who are present at the office. Then later enter the attendance data into the company's internal attendance system. Only the leadership has access rights to enter attendance data into the company's attendance system. This system is considered less effective and efficient. In addition to increasing the workload of the leadership. Attendance is also often hollow or empty when the leader is unable to carry out the attendance process. With an employee attendance system based on the Google Maps range, it is the employee who will carry out the attendance process himself so that the attendance process can be faster, more precise, and accurate.